MnoSR removal in Mycobacterium smegmatis triggers broad transcriptional response to 1,3-propanediol and glucose as sole carbon sources - Płocińska, Renata; Struś, Katarzyna; Korycka-Machała, Małgorzata; Płociński, Przemysław; Kuzioła, Magdalena; Żaczek, Anna; Słomka, Marcin; Dziadek, Jarosław (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe two-component signal transduction systems play an essential role in the adaptation of bacteria to changing environmental conditions. One of them is the MnoSR system involved in the regulation of methylotrophic metabolism in M. smegmatis.MethodsMycobacterium smegmatis mutant strains ΔmnoS, ΔmnoR and ΔmnoS/R lacking functional mnoS, mnoR and both genes were generated using a homologous recombination approach. MnoR recombinant protein was purified by affinity column chromatography. The present study employs molecular biology techniques: cloning strategies, global RNA sequencing, qRT-PCR, EMSA, Microscale thermophoresis, and bioinformatics analysis.Results and discussionThe ∆mnoS, ∆mnoR, and ∆mnoS/R mutant strains were generated and cultured in the presence of defined carbon sources. Growth curve analysis confirmed that inactivation of the MnoSR impairs the ability of M. smegmatis cells to use alcohols such as 1,3-propanediol and ethanol but improves the bacterial growth on ethylene glycol, xylitol, and glycerol. The total RNA sequencing method was employed to understand the importance of MnoSR in the global responses of mycobacteria to limited carbon access and in carbon-rich conditions. The loss of MnoSR significantly affected carbon utilization in the case of mycobacteria cultured on glucose or 1,3-propanediol as sole carbon sources as it influenced the expression of multiple metabolic pathways. The numerous transcriptional changes could not be linked to the presence of evident MnoR DNA-binding sites within the promotor regions for the genes outside of the mno operon. This was confirmed by EMSA and microscale thermophoresis with mutated MnoR binding consensus region. Our comprehensive analysis highlights the system’s vital role in metabolic adaptability, providing insights into its potential impact on the environmental survival of mycobacteria.